Niels Arnfred, Sven Bislev, Anders Eldrup, Anders Hesselholdt, Peter Kragh Jespersen, Morten Sloth (red.), Samfundsplanlægning - en antologi om erfaringer, problemer, perspektiver (1980) - Bruun, Finn (Politica, 1981)
-